Hip osteoarthritis in ex-amateur football players – assessment and rehabilitation - Doru Stoica; Constantin Kamal; Diana Kamal; Mirela Radu (Balneo and PRM Research Journal, 2025)
The study investigated the impact of football on hip osteoarthritis (HOA) in retired amateur players through a two-part research design: a cross-sectional study and a prospective randomized controlled trial (RCT). The cross-sectional component assessed the association between cam morphology and hip disability in former players diagnosed with HOA. The prospective RCT evaluated the effectiveness of a tailored rehabilitation program. Both study groups, the study group (SG – 12 men) and control group (CG – 28 men), were homogeneous in terms of biographical and rheumatic disease features. The study included a comprehensive initial assessment to establish appropriate rehabilitation goals and measures. Key quantitative findings revealed a 30% prevalence of cam morphology among participants. Significant improvements were observed in both groups over time for the Visual Analogue Scale (VAS) and the International Hip Outcome Tool 12 (iHOT12), indicating the effectiveness of the rehabilitation program. The control intervention involved standard rehabilitation practices, which were compared to the tailored approach in the SG. The main findings suggest that tailored rehabilitation strategies are crucial in managing HOA in aging amateur football players, highlighting the need for personalized treatment plans to address the specific challenges faced by this population. These results underscore the importance of early detection and intervention in the natural progression of HOA among football players.